Cytohistopathological evaluation of salivary gland lesions in tertiary care center of Eastern Nepal - Karki, Diksha; Adhikari, Purbesh; Dahal, Mona (Asian Journal of Medical Sciences, 2024)
Background: Salivary gland tumors consist of a group of heterogeneous lesion with complex clinicopathological characteristics. Fine needle aspiration (FNA) cytology has been used as a quick, non-invasive diagnostic tool for the diagnosis of neoplastic and non-neoplastic lesion of salivary gland. Aims and Objectives: The aims and objectives of the study are to perform the cytopathological evaluation of minor and major salivary gland lesions (neoplastic and non-neoplastic) in terms of its various types, frequency, site, demographic distribution and to correlate with histopathology findings whenever available. Materials and Methods: This is a hospital-based 3-year study in which 155 cases of patient underwent FNA cytology for salivary gland swelling (non-neoplastic and neoplastic) of which seven cases were excluded due to scant and inadequate aspirate, and thus, only 148 cases were included in this study and histopathological correlation was available in 42 cases. Any metastatic lesion, repeat samples from same patient were excluded from the study. Results: Out of 148 cases, male patients were 72 (49%) and female patients were 76 (51%) with M: F ratio of 0.9:1. Benign lesion was commonly seen in 31–40 years, non-neoplastic lesion at 41–60 years (n=18, 37.6%), and malignant lesions at 61–90 years (n=9, 37.5%). Parotid was the most common salivary gland involved by neoplastic and non-neoplastic lesion accounting 65.5% (n=97) followed by submandibular gland 29.7% (n=34). Pleomorphic adenoma was most frequently diagnosed among all salivary gland lesions (60%). Mucoepidermoid carcinoma outnumbered the category (14%) of malignant salivary gland lesion. On histopathology correlation, 33 cases were correctly diagnosed in cytopathology whereas 9 cases showed discordant result. FNA cytology sensitivity was 66.6%, specificity was 93.3%, positive predictive value was 80.0%, and negative predictive value was 87.5%, respectively. Diagnostic accuracy was found to be 85.7%. Conclusion: Cytopathology examination of salivary gland can be used as safe and reliable method in primary diagnosis of lesions of salivary gland.